INDIVIDUALIZATION OF ORTHOPEDIC FOOTWEAR: KEY FACTORS IN DESIGN - CHERTENKO, LILIIA; KERNESH, VIKTORIIA; KUZINA, NATALIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article considers the improvement of the method of development and manufacturing of orthopedic footwear taking into account the factors of comfort, functionality and aesthetics on the example of an individual shoe design for a patient with limb shortening. The research used: methods of 3D anthropometric research and analysis of initial information, plastering and scanning of patients’ feet, as well as the reverse engineering method for designing a model of a shoe and an orthopedic insole-compensator for limb shortening. The result of the work is a developed shoe design that meets the individual requirements of the patient by taking into account the factors of anatomical and physiological features of the foot and the functional requirements of the user. Today, the individualization of orthopedic footwear is an important task, since the compliance of footwear with the requirements and anthropometric parameters of the patient affects his comfort and health. Each person has his own anatomical features that need to be taken into account when designing footwear. That is why it is important to develop footwear that takes into account the individual requirements of each person, and for orthopedic footwear this is critically important. Individualized orthopedic footwear, with the right approach to design and production processes, helps to improve foot support, ensuring the correct position when walking and reducing the load on the joints. The use of modern technologies and materials allows you to perform this task effectively. Today, the main task in the manufacture of orthopedic footwear is to create products that meet the individual requirements of each consumer. Properly designed footwear can be a guarantee of improving the functionality of the lower extremities and preventing further complications.